2014
DOI: 10.1017/s0022109014000593
|View full text |Cite
|
Sign up to set email alerts
|

Inside Debt and Mergers and Acquisitions

Abstract: I empirically investigate the relation between chief executive officer (CEO) inside debt holdings and mergers and acquisitions (M&As), and find evidence consistent with the agency theory’s prediction of a negative relation between CEO inside debt holdings and corporate risk taking. Further analysis shows that CEO inside debt holdings are positively correlated with M&A announcement abnormal bond returns and long-term operating performance, but negatively correlated with M&A announcement abnormal sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 61 publications
3
85
0
Order By: Relevance
“…Phan () examines the performance and value implications of CEO inside debt holdings in merger and acquisition activities. Phan finds that firms with high CEO inside debt holdings engage in mergers and acquisitions that lead to positive abnormal bond returns and long‐term operating performance, but result in negative abnormal stock returns.…”
Section: Prior Literature and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Phan () examines the performance and value implications of CEO inside debt holdings in merger and acquisition activities. Phan finds that firms with high CEO inside debt holdings engage in mergers and acquisitions that lead to positive abnormal bond returns and long‐term operating performance, but result in negative abnormal stock returns.…”
Section: Prior Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Liu, Mauer, and Zhang (2014) report that CEO debt-like compensation is positively related to firm cash holdings and that the marginal value of cash to shareholders decreases as the proportion of the CEO's wealth represented by debt-like compensation increases. Phan (2014) examines the performance and value implications of CEO inside debt holdings in merger and acquisition activities. Phan finds that firms with high CEO inside debt holdings engage in mergers and acquisitions that lead to positive abnormal bond returns and long-term operating performance, but result in negative abnormal stock returns.…”
Section: Prior Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Other research finds that inside debt holding decreases (increases) the firm's cost of debt (equity) and decreases the firm's market risk levels (Wei and Yermack, 2011), lowers borrowing costs and reduces the use of debt covenants (Anantharaman, Fang, and Gong, 2014), reduces accounting conservatism (Wang, Xie, and Xin, 2014), and the riskiness of the firm's investment and financing policies (Cassell et al, 2012). In addition, inside debt holdings are positively associated with firm cash holdings (Liu, Mauer, and Zhang, 2014) and abnormal bond returns at merger and acquisition (M&A) announcements (Phan, 2014), and negatively associated with cash holding value (Liu et al, 2014) and abnormal stock returns at M&A announcements (Phan, 2014).…”
Section: Related Literaturementioning
confidence: 99%
“…It is less well known that CEO pay can also be aligned with the interests of debt holders. A growing literature has shown that compensating CEOs with inside debt can lower the risk-taking preferences of CEOs (Edmans and Liu, 2011;Phan, 2014;Bennett et al, 2015;van Bekkum, 2016). Because inside debt is an unsecured and unfunded form of firm debt, it effectively turns CEOs into creditors of their firm.…”
Section: Introductionmentioning
confidence: 99%